Effects of sub-chronic exposure to lead (Pb) and ascorbic acid in juvenile rockfish: Antioxidant responses, MT gene expression, and neurotransmitters. (March 2017) - Kim, Jun-Hwan; Kang, Ju-Chan
Abstract: Juvenile rockfish Sebastes schlegelii were exposed to varying levels of dietary lead (Pb 2+ ) at 0, 120 and 240 mg/L, and ascorbic acid (AsA) at 100, 200 and 400 mg/L for four weeks. Antioxidant responses such as superoxide dismutase (SOD), glutathione S-transferase (GST), and glutathione (GSH) were analyzed to assess oxidative stress. SOD and GST activity in the liver and gills were considerably elevated by dietary Pb. In contrast, GSH levels in the liver and gills were significantly reduced following Pb exposure. High levels of AsA supplementation attenuated the increase in SOD and GST activity and reduction in GSH levels. The metallothionein gene ( MT ) in the liver was notably stimulated by Pb exposure, and AsA supplementation attenuated this increase. With respect to neurotoxicity, acetylcholinesterase (AChE) activity was substantially inhibited in the brain and muscle following Pb exposure. AsA supplementation also attenuated AChE inhibition following Pb exposure. The results of this study presented Pb exposure affected rockfish as toxicity, and AsA was effective to alleviate toxic effects of Pb. Highlights: Antioxidant responses were affected following exposure to dietary Pb. MT gene expression was induced following exposure to Pb. AChE activity was inhibited following exposure to Pb. AsA supplementation effectively attenuated these Pb-induced toxicity.